Preparation method of porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain

By introducing pores into the Cu-Al-Mn-based alloy and cyclic heat treatment, a porous shape memory alloy with 4% to 8% ultra-large compressive elastic strain was prepared, which solved the problem of limited elastic strain in the existing metal alloys, and achieved the effect of high elastic deformation and lightweighting.

CN116479285BActive Publication Date: 2025-03-21WUHAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310360325.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2025-03-21
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

The elastic strains that existing metals and their alloys bear in actual engineering applications are extremely limited, usually less than 0.5%, making it difficult to achieve large elastic deformation.

Method used

By introducing pores, using the regulation of the matrix phase and the porous phase with a high orientation, combined sintering and cyclic heat treatment methods, a porous Cu-Al-Mn-based shape memory alloy with ultra-large compression elastic strain of 4% to 8%.

Benefits of technology

It achieves an ultra-large compression elastic strain of 4% to 8%, exceeding the elastic deformation ability of existing metals and alloys, and has the advantages of lightweight, noise reduction and sound absorption and medium intensity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116479285B_ABST
    Figure CN116479285B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain. By introducing pores into the Cu-Al-Mn shape memory alloy and regulating the highly oriented matrix phase and the pore phase, an ultra-large compressive elastic strain of 4% to 8% is obtained. This value exceeds that of most high-elastic metals reported in the current literature and has great application potential. At the same time, since the alloy has a porous structure, it is more than 10% lighter than alloys of the same volume and composition, and has a good lightweight effect. Third, due to its porous structure, the alloy has the effect of reducing noise and absorbing sound while having ultra-large elasticity. Fourth, the alloy prepared by this method has the characteristics of low elastic modulus (<10GPa). Fifth, the alloy has medium strength, with a compressive limit strength of 300 to 700MPa, which is higher than that of other porous alloys with the same composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shape memory alloys, and in particular to a method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain. Background Art

[0002] Metals and alloys with large elastic deformation can be used as components of mechanical vibration systems and sports equipment because they have large reversible strain and mechanical energy storage. These crystalline metals undergo elastic deformation due to the temporary stretching or contraction of bonds between atoms. The ideal elastic strain of a crystalline metal is the strain when the lattice decomposes itself, so there is an absolutely defect-free upper limit of elastic strain, which is close to 10%. However, due to the presence of factors such as inelastic relaxation caused by discrete dislocations, deformation twins, and stress-induced phase transitions, crystalline metals usually undergo very limited elastic strains in practical engineering applications, generally <0.5%. Therefore, the development of metal crystals that can achieve large elastic deformation has considerable challenges and good application potential.

[0003] In the past many years, many studies have focused on improving the elastic deformation of crystalline metals. Cui Lishan and others from China University of Petroleum developed an in-situ composite material Ni41Ti39Nb20 by combining Nb nanowires with NiTi shape memory alloys, which has a large linear elastic strain of more than 6%. However, the above composite material Ni41Ti39Nb20 with super elasticity is formed by repeated drawing, and the process is complicated and difficult to promote on a large scale.

[0004] Xu Sheng and others from Tohoku University in Japan conducted cyclic heat treatment on the columnar Cu69Al17Mn14 alloy to obtain a bulk Cu-based single crystal alloy, and observed large tensile elastic deformation originating from single-phase reversible lattice strain, with an elastic strain of ~4.3%.

[0005] At present, all metals and their alloys generally suffer from very small elastic deformation. Even the alloys with ultra-large elastic strain reported in the literature have limited elastic deformation. The patent application introduces pores and obtains ultra-large compressive elastic strain of 4% to 8% through the regulation of highly oriented matrix phase and pore phase, which exceeds all metals and their alloys reported in the literature and has the advantage of ultra-large compressive elasticity. In addition, compared with the present application, the high-elastic metals and alloys reported in the literature are all dense block alloys, which have a larger mass under the same volume and composition, and are not suitable for their application. In addition, compared with the present application, the one reported in the literature, therefore, the present application has the advantage of simple process.

[0006] This patent uses a combined sintering method, utilizing the Kirkendall pores formed by the self-diffusion of Al elements in a vacuum high-temperature environment and the interstitial pores formed by crushing the pre-alloy (without introducing additional ones) to jointly form the pores of the alloy, and obtains a porous Cu-Al-Mn shape memory alloy with a strong texture and low-angle grain boundaries through a special heat treatment method. Based on the principle of pore phase and microstructure regulation, a porous Cu-Al-Mn-based shape memory alloy with an ultra-large compressive elastic strain of 4% to 8% is obtained. Summary of the invention

[0007] In view of this, the present invention proposes a method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain, which has a porous Cu-Al-Mn shape memory alloy with strong texture and low-angle grain boundaries. Based on the principle of pore phase and microstructure regulation, a porous Cu-Al-Mn-based shape memory alloy with ultra-large compressive elastic strain of 4% to 8% is obtained.

[0008] The technical solution of the present invention is achieved in this way:

[0009] In one aspect, the present invention provides a method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain, comprising the following steps:

[0010] A, preparation of porous Cu-Al-Mn based shape memory alloy;

[0011] B, subjecting it to cyclic heat treatment, so that the porous Cu-Al-Mn-based shape memory alloy has a porosity of 25-10%, an average pore size of 5-20 μm, a maximum pore size of less than 50 μm, and a preferred grain orientation distribution of <100> ~ <101> The compressive elastic deformation reaches 4-8%, and the elastic modulus is less than 10GPa.

[0012] To prepare the 4% to 8% ultra-large compressive elastic strain porous Cu-Al-Mn-based shape memory alloy of the present invention, two conditions need to be met: (1) porous structure; (2) cyclic heat treatment. If the porosity is too large, the hysteresis curve will be large and the strength will be low; conversely, if the porosity is too small, the porous phase and the collective phase will be unbalanced and the elastic section will be short. In addition, if cyclic heat treatment is not performed, the preferred texture cannot be formed, resulting in the alloy compression curve being similar to that of ordinary polycrystalline alloys.

[0013] On the basis of the above technical solution, preferably, the preparation process of the porous Cu-Al-Mn based shape memory alloy includes:

[0014] A1: Select metal element powders including Cu, Al and Mn, mix them evenly and press them into powder blocks;

[0015] A2: Heat the powder block sample in a vacuum environment or under the protection of an inert gas at a temperature of 550°C to 650°C for a time of 3h to 10h to obtain a pre-alloyed block;

[0016] A3: crush the pre-alloy;

[0017] A4: The crushed pre-alloyed powder is sintered at a sintering pressure of 25MPa to 50MPa, and the temperature is raised to 900°C to 940°C and kept for 10min to 15min to obtain a porous Cu-Al-Mn based shape memory alloy.

[0018] In the above preferred embodiments, the metal element powder has low cost and the raw materials are more readily available, making its preparation process more convenient.

[0019] In the above preferred embodiment, due to the low melting point of Al, if positive pressure sintering is directly performed at 900°C to 940°C in step A4, Al may easily seep out after melting, resulting in a distortion of the element ratio. In the present invention, the Al element is fully diffused and combined with other elements through vacuum pressureless pre-sintering in step A2 to obtain a pre-alloyed block, thereby preventing the Al element from seeping out after melting during the positive pressure sintering process in the subsequent step A4.

[0020] Further preferably, in the step A1, the particle size of the metal element powder material is 200 nm to 400 μm; in the step A3, the pre-alloy is crushed into powder with a particle size of 10 μm to 200 μm.

[0021] In the above preferred embodiment, the porosity of the porous Cu-Al-Mn-based shape memory alloy is controlled by controlling the particle size of the metal element powder feed material, and the pre-alloy powder with a certain porosity and strength is obtained by crushing the pre-alloy.

[0022] Further preferably, in step A1, water flow atomization, air flow atomization or ball milling plus plasma spheroidization is used to prepare the metal element powder.

[0023] Further preferably, in step A4, the crushed pre-alloyed powder is placed in a graphite mold and then placed in a spark plasma device for sintering. Of course, in step A4, as long as the sintering furnace pressure is adjustable, other sintering furnaces, such as a hot press furnace, can also meet the sintering requirements of the present invention.

[0024] Further preferably, in step A4, a staged sintering method is adopted: first, the temperature is increased to 600°C~650°C at a rate of 80°C~120°C / min and kept warm for 10min~15min; then, the temperature is increased to 700°C~800°C at a rate of 80°C / min~120°C / min and kept warm for 10min~15min; then, the temperature is decreased to 900°C~940°C at a rate of 80°C / min~120°C / min and kept warm for 10min~15min, and then the pressure is released and the furnace is cooled.

[0025] On the basis of the above technical solution, preferably, the porous Cu-Al-Mn based shape memory alloy comprises the following element components in mass percentage:

[0026] Al 3~10wt%, Mn 5~20wt.%;

[0027] and alloying elements including Ni 0-3wt.%, Cr 0-2wt.%, Ti 0-2wt.%, B 0-0.5wt.%, Fe 0-3wt.%, or V 0-2wt.%;

[0028] The balance is Cu and necessary impurities.

[0029] All of the above belong to Cu-Al-Mn based shape memory alloys, among which, adding Ni can improve plasticity; adding Cr can improve temperature stability; adding Ti can improve plasticity; adding B can refine grains, improve strength and reduce hysteresis; adding Fe can refine grains, improve strength and reduce hysteresis; adding V can improve strength.

[0030] On the basis of the above technical solution, preferably, in the step B, the porous Cu-Al-Mn based shape memory alloy is subjected to cyclic heat treatment, comprising the following steps:

[0031] B1, isolating the porous Cu-Al-Mn-based shape memory alloy obtained in step A from air, heating it to 500°C to 600°C at a rate of 10°C to 15°C / min, and keeping it at that temperature for 10min to 30min;

[0032] B2, then heat up to 800℃~900℃ at a rate of 10℃ / min~15℃ / min and keep at this temperature for 60min~120min;

[0033] B3, then cool down to 500℃~600℃ at a rate of -3.3℃ / min~-5℃ / min and keep warm for 10min~30min;

[0034] B4, repeat the above steps B1 to B3, and quench after multiple cycles.

[0035] On the basis of the above technical solution, preferably, in the step B, the porous Cu-Al-Mn based shape memory alloy is subjected to cyclic heat treatment, comprising the following steps:

[0036] B1, isolating the porous Cu-Al-Mn-based shape memory alloy obtained in step A from air, and then heating it to 800°C to 900°C at a rate of 10°C / min to 15°C / min and keeping it at that temperature for 10min to 30min;

[0037] B2, then cool down to 500℃~600℃ at a rate of -3.3℃ / min~-5℃ / min and keep warm for 10min~30min;

[0038] B3, then heat up to 800℃~900℃ at 10℃~15℃ / min and keep warm for 60min~120min;

[0039] B4, repeat the above steps B1 to B3, and quench after multiple cycles.

[0040] In the above preferred embodiment, if the temperature in step B2 is too high, the alloy will easily melt and an impurity phase will precipitate; conversely, if the temperature in step B2 is too low, a bainite phase will easily precipitate and dissipation will increase.

[0041] Further preferably, in the step B, the porous Cu-Al-Mn-based shape memory alloy obtained in the step A is wrapped with carbon paper or encapsulated in a vacuum tube to isolate the air; or, an inert gas is introduced into the circulating heat treatment furnace to isolate the air.

[0042] Further preferably, in step B4, the above steps B1 to B3 are repeated for 3 to 10 times.

[0043] Further preferably, in step B4, the quenching condition is water quenching, and the water temperature is 20°C to 30°C.

[0044] The preparation method of the porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain of the present invention has the following beneficial effects compared with the prior art:

[0045] (1) By introducing pores into the Cu-Al-Mn shape memory alloy and regulating the highly oriented matrix phase and the pore phase, an ultra-large compressive elastic strain of 4% to 8% is obtained. This value exceeds that of most high-elastic metals reported in the current literature and has great application potential. At the same time, due to its porous structure, the alloy is more than 10% lighter than alloys of the same volume and composition, and has a good lightweight effect. Third, due to its porous structure, the alloy has the effect of reducing noise and absorbing sound while having ultra-large elasticity. Fourth, the alloy prepared by this method has the characteristics of low elastic modulus (<10GPa). Fifth, the alloy has medium strength, with a compressive limit strength of 500 to 700MPa, which is higher than other porous alloys with the same composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0047] Figure 1 Schematic diagram of heating steps 4, 6 and 7 of Example 1 respectively;

[0048] Figure 2 Compression curves of porous Cu-Al-Mn shape memory alloys obtained in Examples 1, 2, and 4;

[0049] Figure 3 This is a SEM photo of the porous Cu-Al-Mn shape memory alloy obtained in Example 3;

[0050] Figure 4 EBSD grain morphology and color comparison diagram of the porous Cu-Al-Mn shape memory alloy obtained in Example 1;

[0051] Figure 5 EBSD grain boundary angle distribution diagram and inverse pole figure of the porous Cu-Al-Mn shape memory alloy obtained in Example 1. DETAILED DESCRIPTION

[0052] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] Example 1

[0054] This embodiment provides a method for preparing a porous Cu71Al18Mn11 shape memory alloy material obtained by a step-by-step sintering and graded heat treatment method, comprising the following steps:

[0055] Step 1: Select Cu, Al, and Mn element powders atomized by water flow, the aperture of which is 200 mesh, and weigh the metal element powders according to the atomic ratio for mixing;

[0056] Step 2: Place the mixed metal element powder in a planetary ball mill, mix at a ball-to-material ratio of 5:1, 200 r / min, and the mixing time is 24 hours;

[0057] Step 3: Press the mixed powder into small cylindrical pieces in an alloy steel mold;

[0058] Step 4: Place the pressed cylindrical block in a vacuum sintering furnace and maintain the vacuum degree at 1.2*10 -2 Pa, kept at 620℃ for 5 hours, such as Figure 1 As shown;

[0059] Step 5: Grind the pre-alloyed block after heat preservation to crush it into powder with a particle size of 50μm to 100μm;

[0060] Step 6: The crushed powder is placed in a graphite mold, compacted with a pressure rod, and then placed in a spark plasma furnace for sintering by a segmented sintering method. The sintering pressure is 45 MPa, and the final forming temperature is 920°C. The temperature is first raised to 620°C at a rate of 100°C / min and kept for 10 minutes; then raised to 750°C at a rate of 100°C / min and kept for 10 minutes; then raised to 920°C at a rate of 100°C / min and kept for 10 minutes, and then the pressure is released and cooled with the furnace. Figure 1 As shown;

[0061] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 900℃ at 10℃ / min and keep it for 10min, then reduce the temperature to 550℃ at -3.3℃ / min and keep it for 20min, then heat it to 900℃ at 10℃ / min and keep it for 60min, repeat this operation 6 times and quench it to room temperature. Figure 1 shown.

[0062] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 12%, a maximum pore size of 31 μm, and a preferred grain orientation distribution of <100> ~ <101> Between, such as Figure 4 and 5 As shown, the maximum elastic deformation is 8%. Figure 2As shown in the 8% strain curve, the elastic modulus is 8.8 GPa.

[0063] Example 2

[0064] This embodiment provides a method for preparing a porous Cu71Al18Mn11 shape memory alloy material obtained by a step-by-step sintering and graded heat treatment method, comprising the following steps:

[0065] Step 1: Select Cu, Al, and Mn element powders atomized by water flow, the aperture of which is 50 mesh, and weigh the metal element powders according to the atomic ratio for mixing;

[0066] Step 2: Place the mixed metal element powder in a planetary ball mill, mix at a ball-to-material ratio of 5:1, 200 r / min, and the mixing time is 30 hours;

[0067] Step 3: Press the mixed powder into small cylindrical pieces in an alloy steel mold;

[0068] Step 4: Place the pressed cylindrical block in a vacuum sintering furnace and maintain the vacuum degree at 1.2*10 -2 Pa, kept at 650 °C for 10 hours;

[0069] Step 5: Grind the pre-alloyed block after heat preservation to crush it into powder with a particle size of 200μm to 300μm;

[0070] Step 6: The crushed powder is placed in a graphite mold, compacted with a pressure rod, and then placed in a discharge plasma furnace for sintering by a segmented sintering method. The sintering pressure is 25 MPa, and the final forming temperature is 940°C; wherein, the temperature is first raised to 620°C at a rate of 80°C / min and kept for 10 minutes; then the temperature is raised to 750°C at a rate of 80°C / min and kept for 10 minutes; then the temperature is raised to 940°C at a rate of 80°C / min and kept for 10 minutes, and then the pressure is released and the furnace is cooled;

[0071] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 850°C at 12°C / min and keep it for 30 minutes, then reduce the temperature to 500°C at -4°C / min and keep it for 30 minutes, then heat it to 850°C at 12°C / min and keep it for 90 minutes, repeat this operation 3 times and then quench it to room temperature.

[0072] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 19%, a maximum pore size of 19 μm, and a preferred grain orientation distribution of <100> ~ <101> The maximum elastic deformation is 4%. Figure 2 As shown in the 4% strain curve, the elastic modulus is 5.8 GPa.

[0073] Example 3

[0074] This embodiment provides a method for preparing a porous Cu71Al18Mn11 shape memory alloy material obtained by a step-by-step sintering and graded heat treatment method, comprising the following steps:

[0075] Step 1: Select Cu, Al, and Mn element powders atomized by water flow, the aperture of which is 500 mesh, and weigh the metal element powders according to the atomic ratio for mixing;

[0076] Step 2: Place the mixed metal element powder in a planetary ball mill, mix at a ball-to-material ratio of 5:1, 200 r / min, and the mixing time is 12 hours;

[0077] Step 3: Press the mixed powder into small cylindrical pieces in an alloy steel mold;

[0078] Step 4: Place the pressed cylindrical block in a vacuum sintering furnace and maintain the vacuum degree at 1.2*10 -2 Pa, kept at 550 °C for 3 hours;

[0079] Step 5: Grind the pre-alloyed block after heat preservation to crush it into powder with a particle size of 10μm to 100μm;

[0080] Step 6: The crushed powder is placed in a graphite mold, compacted with a pressure rod, and then placed in a spark plasma furnace for sintering by a segmented sintering method. The sintering pressure is 50 MPa, and the final forming temperature is 900 ° C. The temperature is first raised to 620 ° C at a rate of 120 ° C / min and kept for 10 minutes; then the temperature is raised to 750 ° C at a rate of 120 ° C / min and kept for 10 minutes; then the temperature is raised to 900 ° C at a rate of 120 ° C / min and kept for 10 minutes, and then the pressure is released and cooled with the furnace;

[0081] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 800°C at 15°C / min and keep it for 20 minutes, then reduce the temperature to 600°C at -5°C / min and keep it for 10 minutes, then heat it to 800°C at 15°C / min and keep it for 120 minutes. Repeat this operation 5 times and then quench it to room temperature.

[0082] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 10% and a maximum pore size of 32 μm. Figure 3 As shown, the preferred orientation of the grains is distributed in <100> ~ <101> The maximum elastic deformation is 7.8% and the elastic modulus is 5GPa.

[0083] Example 4

[0084] This embodiment is basically the same as Embodiment 1, except that this embodiment provides a method for preparing a porous Cu72Al18Mn10 shape memory alloy material obtained by step-by-step sintering and graded heat treatment.

[0085] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 12%, a maximum pore size of 28 μm, and a preferred grain orientation distribution of <100> ~ <101> The maximum elastic deformation is 6%. Figure 2 As shown in the 6% strain curve, the elastic modulus is 4.9 GPa.

[0086] Example 5

[0087] This embodiment is basically the same as Embodiment 1, except that this embodiment provides a method for preparing a porous (Cu71Al18Mn11)98-Ti2 shape memory alloy material obtained by step-by-step sintering and graded heat treatment: in step one, water-atomized Cu, Al, Mn, and Ti element powders are selected.

[0088] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 13%, a maximum pore size of 30 μm, and a preferred grain orientation distribution of <100> ~ <101> The maximum elastic deformation is 6.2% and the elastic modulus is 6.1 GPa.

[0089] Example 6

[0090] This embodiment is basically the same as Embodiment 1, except that:

[0091] Step 1: Select Cu, Al, and Mn element powders atomized by water flow, with a particle size of 50nm to 100nm. Step 5: Grind the pre-alloyed block after heat preservation fully and crush it into powder with a particle size of 30μm to 150μm.

[0092] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 10%, a maximum pore size of 26 μm, and a preferred grain orientation distribution of <100> ~ <101> The maximum elastic deformation is 7.1% and the elastic modulus is 6.8 GPa.

[0093] By comparing Example 1 and Example 6, it is explained that if the particle size of the metal element powder is too small, the elastic deformation amount will decrease.

[0094] Example 7

[0095] This embodiment is basically the same as Embodiment 1, except that:

[0096] Step 1: Select Cu, Al, and Mn element powders atomized by water flow, with a particle size of 400μm to 500μm. Step 5: Grind the pre-alloyed block that has been insulated thoroughly and crush it into powder with a particle size of 400μm to 500μm.

[0097] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 18%, a maximum pore size of 38 μm, and a preferred grain orientation distribution of <100> ~ <101> The maximum elastic deformation is 5.0% and the elastic modulus is 2.1 GPa.

[0098] By comparing Example 1 and Example 7, it is explained that if the particle size of the metal element powder is too large, the porosity will be large and the elastic deformation will be reduced.

[0099] Example 8

[0100] This embodiment is basically the same as Embodiment 1, except that:

[0101] Step 6: Sintering pressure is 10MPa;

[0102] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 29%, a maximum pore size of 30 μm, and a preferred grain orientation distribution of <100> ~ <101> The maximum elastic deformation is 3% and the elastic modulus is 2.1GPa.

[0103] By comparing Example 1 and Example 8, it is explained that if the positive pressure sintering (SPS sintering) pressure is too low, it will lead to large porosity and small elastic deformation.

[0104] Example 9

[0105] This embodiment is basically the same as Embodiment 1, except that:

[0106] Step 6: Sintering pressure is 100MPa;

[0107] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 5%, a maximum pore size of 5 μm, and a preferred grain orientation distribution of <100> ~ <101> The maximum elastic deformation is 2.8% and the elastic modulus is 15GPa.

[0108] By comparing Example 1 and Example 9, it can be shown that if the positive pressure sintering (SPS sintering) is too high, the porosity will be low, the elastic modulus will be large, and the elastic deformation will be small.

[0109] Example 10

[0110] This embodiment is basically the same as Embodiment 1, except that:

[0111] Only steps 1 to 6 are performed, and the cyclic heat treatment process of step 7 is not performed.

[0112] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 12%, a maximum pore size of 31 μm, no preferred orientation of grains, a maximum elastic deformation of 2%, and an elastic modulus of 4.5 GPa.

[0113] By comparing Example 1 and Example 10, it is explained that if only vacuum pressureless sintering and positive pressure sintering are performed without cyclic heat treatment, the grains will have no preferential orientation and the elastic deformation will decrease.

[0114] Embodiment 11

[0115] This embodiment is basically the same as Embodiment 1, except that:

[0116] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 550°C at 10°C / min and keep it for 20 minutes, then heat it to 900°C at 10°C / min and keep it for 60 minutes, then drop the temperature to 550°C at -3.3°C / min and keep it for 20 minutes. Repeat this operation 6 times and then quench it to room temperature.

[0117] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 13%, a maximum pore size of 30 μm, and a preferred grain orientation distribution of <100> ~ <101> The maximum elastic deformation is 7.8% and the elastic modulus is 5.1 GPa.

[0118] By comparing Example 1 and Example 11, it is shown that if the order of the cyclic heat treatment process is changed, there is basically no effect on the elastic deformation of the alloy.

[0119] Example 12

[0120] This embodiment is basically the same as embodiment 1, except that the first stage sintering temperature in step 7 is lower:

[0121] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 700°C at 12°C / min and keep it for 30 minutes, then reduce the temperature to 500°C at -4°C / min and keep it for 30 minutes, then heat it to 850°C at 12°C / min and keep it for 90 minutes, repeat this operation 3 times and then quench it to room temperature.

[0122] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 14%, a maximum pore size of 30 μm, no preferred orientation of grains, a maximum elastic deformation of 3%, and an elastic modulus of 6.5 GPa.

[0123] By comparing Example 1 and Example 12, it is explained that the low sintering temperature in the first stage of step seven will result in the failure to form a preferred texture and a decrease in the elastic deformation.

[0124] Embodiment 13

[0125] This embodiment is basically the same as embodiment 1, except that the first stage sintering temperature in step 7 is higher:

[0126] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 1000°C at 12°C / min and keep it for 30 minutes, then reduce the temperature to 500°C at -4°C / min and keep it for 30 minutes, then heat it to 850°C at 12°C / min and keep it for 90 minutes, repeat this operation 3 times and then quench it to room temperature.

[0127] The porous Cu-Al-Mn shape memory alloy obtained through the above steps has a porosity of 5%, a maximum pore size of 10 μm, no grain preferential orientation, a maximum elastic deformation of 5%, and an elastic modulus of 4.3 GPa.

[0128] By comparing Example 1 and Example 11, it is explained that the high sintering temperature in the first stage of step seven will result in the failure to form a preferred orientation and a decrease in the elastic deformation.

[0129] Embodiment 14

[0130] This embodiment is basically the same as embodiment 1, except that the second stage sintering temperature in step 7 is lower:

[0131] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 900°C at 12°C / min and keep it for 30 minutes, then reduce the temperature to 400°C at -4°C / min and keep it for 30 minutes, then heat it to 850°C at 12°C / min and keep it for 90 minutes, repeat this operation 3 times and then quench it to room temperature.

[0132] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 12.5%, a maximum pore size of 30 μm, no preferred orientation of grains, a maximum elastic deformation of 3.8%, and an elastic modulus of 6.2 GPa.

[0133] By comparing Example 1 and Example 11, it is explained that the low sintering temperature in the second stage of step seven will lead to the precipitation of bainite phase, the grains have no preferential orientation, and the elastic deformation amount decreases.

[0134] Embodiment 15

[0135] This embodiment is basically the same as embodiment 1, except that the second stage sintering temperature in step 7 is higher:

[0136] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 900°C at 12°C / min and keep it for 30 minutes, then reduce the temperature to 700°C at -4°C / min and keep it for 30 minutes, then heat it to 850°C at 12°C / min and keep it for 90 minutes, repeat this operation 3 times and then quench it to room temperature.

[0137] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 10.2%, a maximum pore size of 32 μm, no preferred orientation of grains, a maximum elastic deformation of 3.9%, and an elastic modulus of 6.9 GPa.

[0138] By comparing Example 1 and Example 11, it is explained that the high sintering temperature in the second stage of step seven will lead to no preferential orientation of grains and a decrease in elastic deformation.

[0139] Example 16

[0140] This embodiment is basically the same as embodiment 1, except that the sintering temperature in the third stage in step 7 is lower:

[0141] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 900°C at 12°C / min and keep it for 30 minutes, then reduce the temperature to 500°C at -4°C / min and keep it for 30 minutes, then heat it to 700°C at 12°C / min and keep it for 90 minutes, repeat this operation 3 times and then quench it to room temperature.

[0142] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 12.4%, a maximum pore size of 31 μm, no preferred orientation of grains, a maximum elastic deformation of 3.9%, and an elastic modulus of 7.2 GPa.

[0143] By comparing Example 1 and Example 11, it is explained that the low sintering temperature in the third stage of step seven will result in no preferential orientation of grains and a decrease in elastic deformation.

[0144] Embodiment 17

[0145] This embodiment is basically the same as embodiment 1, except that the sintering temperature in the third stage of step 7 is higher:

[0146] Step 7: Wrap the alloy after the above steps with carbon paper, place it in a muffle furnace and heat it to 900°C at 12°C / min and keep it for 30 minutes, then cool it to 500°C at -4°C / min and keep it for 30 minutes, then heat it to 1000°C at 12°C / min and keep it for 90 minutes, repeat this operation 3 times and then quench it to room temperature.

[0147] The porous Cu-Al-Mn shape memory alloy obtained by the above steps has a porosity of 5%, a maximum pore size of 11 μm, no preferred orientation of grains, a maximum elastic deformation of 2.6%, and an elastic modulus of 11.2 GPa.

[0148] By comparing Example 1 and Example 11, it is explained that the high sintering temperature in the third stage of step seven will lead to no preferential orientation of grains and a decrease in elastic deformation.

[0149] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain, characterized in that: The following steps are included: A, preparation of porous Cu-Al-Mn based shape memory alloy; B, subjecting it to cyclic heat treatment, so that the porous Cu-Al-Mn-based shape memory alloy has a porosity of 25-10%, an average pore size of 5-20 μm, a maximum pore size of less than 50 μm, and a preferred grain orientation distribution of <100> ~ <101> The compressive elastic deformation reaches 4~8%, and the elastic modulus is less than 10Gpa; The preparation process of the porous Cu-Al-Mn based shape memory alloy comprises: A1: Select metal element powders including Cu, Al and Mn, mix them evenly and press them into powder blocks; A2: Heat the powder block sample in a vacuum environment or under the protection of an inert gas at a temperature of 550°C to 650°C for a time of 3h to 10h to obtain a pre-alloyed block; A3: crush the pre-alloy; A4: The crushed pre-alloyed powder is sintered at a sintering pressure of 25 MPa ~50 MPa, and the temperature is raised to 900℃~940℃ and kept for 10min~15min to obtain a porous Cu-Al-Mn based shape memory alloy.

2. The method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain according to claim 1, characterized in that: In the step A1, the particle size of the metal element powder material is 200nm~300μm; in the step A3, the pre-alloy is crushed into powder with a particle size of 10μm~300μm.

3. The method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain according to claim 1, characterized in that: In the step A1, water flow atomization, air flow atomization or ball milling plus plasma spheroidization is selected to prepare the metal element powder.

4. The method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain according to claim 1, characterized in that: In the step A4, the crushed pre-alloyed powder is placed in a graphite mold and then placed in a spark plasma device for sintering.

5. The method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain according to claim 1, characterized in that: The porous Cu-Al-Mn-based shape memory alloy comprises the following element components in mass percentage: Al 3~10wt%, Mn 5~20wt.; and alloying elements including Ni 0~3wt.%, Cr 0~2wt.%, Ti 0~2wt.%, B 0~0.5wt.%, Fe 0~3wt.% or V 0~2wt.%; The balance is Cu and necessary impurities.

6. The method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain according to claim 1, characterized in that: In the step B, the porous Cu-Al-Mn based shape memory alloy is subjected to a cyclic heat treatment, comprising the following steps: B1, isolating the porous Cu-Al-Mn-based shape memory alloy obtained in step A from air, heating it to 500°C~600°C at a rate of 10°C~15°C / min and keeping it at that temperature for 10min~30min; B2, then heat up to 800℃~900℃ at a rate of 10℃ / min~15℃ / min and keep at this temperature for 60min~120min; B3, then cool down to 500℃~600℃ at a rate of -3.3℃ / min~-5℃ / min and keep warm for 10min~30min; B4, repeat the above steps B1 to B3, and quench after multiple cycles.

7. The method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain according to claim 1, characterized in that: In the step B, the porous Cu-Al-Mn based shape memory alloy is subjected to a cyclic heat treatment, comprising the following steps: B1, isolating the porous Cu-Al-Mn-based shape memory alloy obtained in step A from air, and then heating it to 800°C~900°C at a rate of 10°C / min~15°C / min and keeping it at that temperature for 10min~30min; B2, then cool down to 500℃~600℃ at a rate of -3.3℃ / min~-5℃ / min and keep warm for 10min~30min; B3, then heat up to 800℃~900℃ at 10℃~15℃ / min and keep warm for 60min~120min; B4, repeat the above steps B1 to B3, and quench after multiple cycles.

8. The method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain according to claim 7 or 6, characterized in that: In the step B, the porous Cu-Al-Mn-based shape memory alloy obtained in the step A is wrapped with carbon paper or encapsulated in a vacuum tube to isolate the air; or, an inert gas is introduced into the circulating heat treatment furnace to isolate the air.

9. The method for preparing a porous Cu-Al-Mn-based alloy with ultra-large compressive elastic strain according to claim 7 or 6, characterized in that: In step B4, the above steps B1 to B3 are repeated for 3 to 10 times.

Citation Information

Patent Citations

  • Preparation method of porous CuAlMn shape memory alloy with controllable pore structure parameters

    CN102191394A